2014
DOI: 10.3906/sag-1210-94
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of total thyroidectomies carried out through LigaSure and Harmonic Scalpel: a retrospective study

Abstract: A 10-month-old, unilateral cryptorchid, male English bulldog underwent urethropexy for the treatment of urethral prolapse. Six hours after surgery the dog developed dysuria, haematuria, discomfort, severe penile oedema, inflammation, and inability to extrude the penis from the prepuce. Urethral patency was restored by placing an indwelling catheter into the urethral lumen. Penile swelling was managed with cold and warm compresses for 2 days, and antibiotics, nonsteroidal anti-inflammatory drugs, and opioids fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
8
2
Order By: Relevance
“…The operative times of our three groups were longer than those of Peker et al. [12] study; Conventional Technique (CT), HS and LigaSure mean and SD were 92.92 ± 12.12, 60.13 ± 12.98 and 60.66 ± 11.90 respectively with P-value = 0.00. Peker et al.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…The operative times of our three groups were longer than those of Peker et al. [12] study; Conventional Technique (CT), HS and LigaSure mean and SD were 92.92 ± 12.12, 60.13 ± 12.98 and 60.66 ± 11.90 respectively with P-value = 0.00. Peker et al.…”
Section: Discussioncontrasting
confidence: 58%
“…Regarding the hospital stay, the three groups; CSL, HS, MAX showed comparable hospital stays; mean ± SD 2.7 ± 0.6 day, 2.6 ± 1 day and 2.8 ± 0.7 day respectively with average of 2.8 ± 0.7 days with no statistically significant difference, P-value = 0.268, while Peker et al. [12] study showed comparable hospital stays in the three groups; CT, HS and LigaSure 1.7 ± 0.60 day,1.7 ± 0.65 day and 1.8 ± 0.78 day respectively with no statistically significant difference P-value = 0.315. Nadim Khan et al.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations